(untitled) (Jewish Thought, 2023)
It is with great pride that we present the fifth issue of the annual journal, Jewish Thought, sponsored by the Goldstein-Goren International Center for Jewish Thought at Ben-Gurion University of the Negev. This issue is devoted to the topic of hopes, dreams and aspirations in Jewish thought. It consists of 15 articles – 11 in Hebrew and 4 in English. Many of the contributions are based on lectures on this topic delivered at the international conference in Jewish thought sponsored by the center in May 2022. The head of the organizing committee was Prof. Adiel Kadari, who was invited to be a guest editor of this issue. As in the case of the journal’s four previous issues, most of the articles in this issue were written by established scholars, while some were written by young scholars who are at the beginning of their scholarly career. All submitted articles underwent a rigorous selection process involving at least two reviewers